Peranan Employee Stock Ownership Plan dalam Pengaruh Value Added Intellectual Capital terhadap Financial Performance - Yeshinta, Trivena (Business Accounting Review, 2015)
This study aimed to examine the affect of the value added intellectual capital to the financial performance and the role of employee stock ownership plan. This study used dummy variable that is employee stock ownership plan. The sample used in this study is a public company financial sector. The hypothesis in this study tested by using multiple regression. The measurement of value added intellectual capital used the method of Pulic (2004) to be associated with profitability (return on investment and return on equity), market value (market-to-book ratio, earing per share and Tobins q), and productivity (asset turnover and employee performance) and also to see if there were differences between firms that do not apply to the ESOP.